Need Analysis of Science Textbook Based Jambi Local Wisdom to Improve Science Literacy of SMPN 7 Muaro Jambi - Jufrida Jufrida; Fibrika Rahmat Basuki; Erina Sawitri; Elsi Afriani (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2019)
This study aims to analyze the need for science books based on Jambi local wisdom to improve student literacy at SMPN 7 Muaro Jambi. This research is a qualitative descriptive study. The subjects of this study were science teachers and 46 seventh grade students at SMPN 7 Muaro Jambi. The research data was collected by observation, interview, and questionnaire. Data analysis techniques were carried out descriptively. This study shows that 1) textbooks used in schools as a source of learning science have not integrated local wisdom and there are no scientific literacy questions, 2) students have high learning motivation and positive attitudes towards science, 3) supporting facilities including teaching materials and the science laboratory is adequate, 4) material that can be integrated with Jambi local wisdom including the IPA object and its observations, temperature and changes, and heat and displacement.